Disentangling the Role of Management Control Systems for Product and Process Innovation in Different Contexts. Issue 4 (8th August 2019) - Guo, Bing; Paraskevopoulou, Evita; Santamaría Sánchez, Luis
ABSTRACT: This paper studies the relationship between the use of management control systems and different types of innovation (product and process), taking into account innovation contexts (high-tech versus low-tech sectors). We develop and test our hypotheses based on a large sample of Spanish manufacturing firms and find that input controls have a positive association only with process innovation in both innovation contexts. Behavior controls have similar effects on both types of innovation outcomes for high-tech firms, while they have stronger positive associations with process than with product innovation for low-tech firms. Output controls are equally relevant for product and process innovation in both contexts.